Respiratory Motion-Registered Isotropic Whole-Heart T2 Mapping in Patients With Acute Non-ischemic Myocardial Injury - Dorniak, Karolina; Di Sopra, Lorenzo; Sabisz, Agnieszka; Glinska, Anna; Roy, Christopher W.; Gorczewski, Kamil; Piccini, Davide; Yerly, Jérôme; Jankowska, Hanna; Fijałkowska, Jadwiga; Szurowska, Edyta; Stuber, Matthias; et al. (Frontiers in Cardiovascular Medicine, 2021)
Background: T2 mapping is a magnetic resonance imaging technique that can be used to detect myocardial edema and inflammation. However, the focal nature of myocardial inflammation may render conventional 2D approaches suboptimal and make whole-heart isotropic 3D mapping desirable. While self-navigated 3D radial T2 mapping has been demonstrated to work well at a magnetic field strength of 3T, it results in too noisy maps at 1.5T. We therefore implemented a novel respiratory motion-resolved compressed-sensing reconstruction in order to improve the 3D T2 mapping precision and accuracy at 1.5T, and tested this in a heterogeneous patient cohort. Materials and Methods: Nine healthy volunteers and 25 consecutive patients with suspected acute non-ischemic myocardial injury (sarcoidosis, n=19; systemic sclerosis, n=2; acute graft rejection, n=2 and myocarditis, n=2) were included. The free-breathing T2 maps were acquired as three ECG-triggered T2-prepared 3D radial volumes. A respiratory motion-resolved reconstruction was followed by image registration of the respiratory states and pixel-wise T2 mapping. The resulting 3D maps were compared to routine 2D T2 maps. The T2 values of segments with and without late gadolinium enhancement (LGE) were compared in the patients. Results: In the healthy volunteers, the myocardial T2 values obtained with the 2D and 3D techniques were similar (45.8±1.8ms vs 46.8±2.9ms, respectively; P=0.33. Conversely, in patients, T2 values did differ between 2D (46.7±3.6ms) and 3D techniques (50.1±4.2ms, P=0.004). Moreover, with the 2D technique, T2 values of the LGE-positive segments were similar to those of the LGE-negative segments (T2LGE-= 46.2±3.7ms vs T2 LGE+=47.6±4.1ms; P=0.49), whereas the 3D technique did show a significant difference (T2LGE-= 49.3±6.7ms versus T2LGE+=52.6±8.7ms, P=0.006). Conclusion: Respiratory motion-registered 3D radial imaging at 1.5T led to sharp and accurate isotropic 3D whole-heart T2 maps, both in the healthy volunteers and in a small patient cohort with suspected non-ischemic myocardial injury. Significantly higher T2 values were found in patients as compared to controls in 3D but not in 2D, suggestive of the technique's potential to increase the sensitivity of CMR at earlier stages of disease. Further study will be needed to demonstrate its accuracy.